Improved impression cytology techniques for the immunopathological diagnosis of superficial viral infections. Issue 11 (1st November 1997) - Thiel, M A; Bossart, W; Bernauer, W
Abstract : BACKGROUND: For epidemiological and therapeutic reasons early diagnosis of superficial viral infections is crucial. Conventional microbiological techniques are expensive, time consuming, and not sufficiently sensitive. In this study impression cytology techniques were evaluated to analyse their diagnostic potential in viral infections of the ocular surface. METHOD: A Biopore membrane device instead of the original impression cytology technique was used to allow better quality and handling of the specimens. The impressions were processed, using monoclonal antibodies and immunoperoxidase or immunofluorescence techniques to assess the presence of herpes simplex virus, varicella zoster virus, or adenovirus antigens. Ocular surface specimens from healthy individuals (n=10) and from patients with suspected viral surface disease (n=19) were studied. Infected and non-infected cell cultures served as controls. RESULTS: This modified technique of impression cytology allowed the collection of large conjunctival and corneal epithelial cell layers with excellent morphology. Immunocytological staining of these samples provided diagnostic results for all three viruses in patients with viral surface disease. CONCLUSIONS: The use of Biopore membrane devices for the collection of ocular surface epithelia offers new diagnostic possibilities for external eye diseases. Immunopathological methods that are applied directly on these membrane devices can provide virological results within 1–4 hours. This contributes considerably to the clinical management of patients with infectious diseases of the ocular surface.